2022
DOI: 10.53318/msp.v11i2.2186
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition aigüe sévère chez les enfants de moins de 6 mois : Cas de l’hôpital de Sikasso

Abstract: Introduction : La malnutrition aigüe demeure un problème de santé publique. Durant les six premiers mois de la vie, une nutrition adaptée est essentielle pour une croissance appropriée ainsi que la formation et le développement du système nerveux. La malnutrition chez les nourrissons de moins de 6 mois est un fléau et reste peu étudié. L’objectif de cette étude était d’évaluer la prévalence de la malnutrition aigüe sévère chez les enfants de moins de 6 mois au service de pédiatrie de l’hôpital de Sikasso. Méth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These results are similar to those of Kabore et al 58.73% of malnourished children were mixed breastfed [11]. Cissouma et al, who reported in their study that 17.46% of malnourished children were exclusively breastfed [1].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are similar to those of Kabore et al 58.73% of malnourished children were mixed breastfed [11]. Cissouma et al, who reported in their study that 17.46% of malnourished children were exclusively breastfed [1].…”
Section: Discussionsupporting
confidence: 90%
“…Malnutrition is a pathological state resulting from the relative or absolute deficiency or excess of one or more essential nutrients, whether manifested clinically or detectable only by biochemical, anthropometric or physiological analyses [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation